Development of Agro-tourism to optimize Village Potential in Mekarwangi Village, Sindangkerta District, West Bandung Regency - Arief Rosyidie; Abadi Raksapati; Yani Adriani (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
Tourism village innovation through the development of agro-tourism villages is an effort to encourage village development based on agricultural and plantation potentials owned by Mekarwangi Village, Sindangkerta District, West Bandung Regency. The implementation of activities is carried out with a participatory approach through three main stages, firstly increasing the capacity of the community to understand tourism, secondly increasing the institutional capacity of Kelompok Sadar Wisata (Pokdarwis), and thirdly testing various tourism products that have been produced. This activity resulted in several things, namely the identification of potential tourist attractions, the formation of Kelompok Sadar Wisata (Pokdarwis), the establishment of a pioneering Kampung Ganyol, the arrangement of the mekarwangi agrotourism village tour package, and the creation of an increase in the quality of agrohomestays.